Lie Symmetry Analysis for the General Classes of Generalized Modified Kuramoto-Sivashinsky Equation. (25th October 2021) - Qi, Rong; Munir, Muhammad Mobeen; Younas, Nazish; Idrees, Muhammad; Liu, Jia-Bao
Abstract : Lie symmetry analysis of differential equations proves to be a powerful tool to solve or at least reduce the order and nonlinearity of the equation. Symmetries of differential equations is the most significant concept in the study of DE's and other branches of science like physics and chemistry. In this present work, we focus on Lie symmetry analysis to find symmetries of some general classes of KS-type equation. We also compute transformed equivalent equations and some invariant solutions of this equation.